Heart disease in pregnancy. (September 2022) - Joy, Eleanor; English, Kate
Abstract: Heart disease has remained the leading cause of maternal mortality for the last 20 years, with evidence that in over a quarter of cases the outcome could have been different had there been an improvement of care. Education of all health professionals involved in the care of pregnant patients is paramount in improving the outcomes for these women, through early detection of cardiac pathology and prompt investigation and management. Patients with known cardiac disease should be given pre-pregnancy counselling to enable them to make informed choices regarding contraception and reproduction, both natural and assisted.